HISTORY EDUCATION CURRICULUM IN INDONESIA - Dwita Aprilla Amir; Bahri Bahri (Yayasan Amanah Nur Aman, 2026)
The curriculum is a fundamental component of the education system, determining the direction, objectives, and learning process. In the context of history education in Indonesia, the curriculum plays a crucial role in developing students' historical awareness, national identity, and national character. This article aims to analyze the development of the history education curriculum in Indonesia and the shifting learning paradigms that have occurred over time. This research uses a qualitative method with a literature study approach that analyzes various sources, books, scientific journals, and educational policy documents. The results of the study indicate that the history education curriculum in Indonesia has undergone a transformation, shifting from a narrative and indoctrinative approach to a competency-based approach and historical thinking. This change is also marked by a shift from a teacher-centered learning model to a student-centered one. Furthermore, recent curricula, such as the 2013 Curriculum and the Merdeka Curriculum, provide greater scope for the development of critical thinking skills, historical source analysis, and project-based learning. However, the implementation of the history curriculum still faces various challenges, such as low student interest in learning, limited teacher competency, and the lack of utilization of digital technology in history learning. Therefore, strengthening historical literacy, pedagogical innovation, and technology integration are crucial factors in developing future history education curricula.